THE INFLUENCE OF REGIONAL ORIGINAL INCOME, GENERAL ALLOCATION FUNDS, SPECIAL ALLOCATION FUNDS ON ECONOMIC GROWTH AND HUMAN DEVELOPMENT INDEX (Study on Regency/City Government of East Java Province Year 2020-2022) - Nur Indah Mukaromah; Made Kembar Sri Budhi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The aim of this research is to determine the effect of Regional Original Income (PAD), General Allocation Funds (DAU), and Special Allocation Funds (DAK) on the Human Development Index (HDI) with Economic Growth as a mediating variable. The sample used in this research was 38 districts/cities in East Java during the period 2020 to 2022. The research method used was path analysis. The results obtained show that: (1) PAD has a positive and significant effect on economic growth, DAU has a negative and significant effect on economic growth, DAK has a positive and significant effect on economic growth; (2) PAD has a positive and significant effect on HDI, DAU has a negative and insignificant effect on HDI, DAK has a negative and significant effect on HDI, economic growth has a positive and significant effect on HDI; (3) PAD has an indirect and significantly positive effect on HDI through economic growth, DAU has an indirect and significantly negative effect on HDI through economic growth, and DAK has an indirect and significantly positive effect on HDI through economic growth.